Effects of Gryllus bimaculatus Powder on Physicochemical Properties and Consumer Acceptability of 3D-Printed Gluten-Free Chocolate Cookies Using Survival Analysis - Woonseo Baik; Dongju Lee; Youngseung Lee (Foods, 2025)
To mitigate consumer aversion toward edible insects, it is essential to determine the optimal level of insect powder by considering consumer acceptability. In this study, gluten-free (GF) chocolate cookies were manufactured using 3D printing with varying concentrations (0, 3, 6, 9, 12, and 15%) of Gryllus bimaculatus (GB) powder. Physicochemical properties, sensory perception using rate-all-that-apply questions, and consumer acceptability using survival analysis were evaluated. The effects of GB powder concentration on the proximate composition, pH, color attributes, physical properties, 3D printing performance, and post-processing of the cookies were analyzed and discussed. As the concentration of GB powder increased, crude protein, ash, crude fat, a*, and mechanical force increased, while L*, b*, and the pH of both the dough and cookies decreased. Consumer tests showed a negative correlation between GB concentration and consumer acceptability, with cookies containing 3% GB receiving the highest overall liking scores. Principal component analysis and partial least squares regression showed that lower GB levels enhanced positive sensory attributes such as sweetness, chocolate flavor, and moistness, whereas higher levels intensified bitter taste and astringency, contributing to reduced acceptability. According to survival analysis, the GB concentration at which 50% of consumers were predicted to reject the product was estimated at 5.23%, indicating the necessity to limit GB incorporation below this threshold to ensure consumer acceptance. This study provides a comprehensive understanding of the quality characteristics and consumer acceptability of insect-based GF cookies, offering valuable insights for future product development and market applications.